(untitled) (Universal International Scientific Journal, 2026)
In this paper, a catalog of 408 galaxy groups has been compiled. The number of galaxies in the groups ranges from 5 to 30. The physical parameters of the groups, such as right ascension, declination, luminosity, radial velocity, velocity dispersion, R magnitude, and B magnitude, are presented. The empirical relationship between each parameter has been statistically analyzed.